POTENSI SPAGHETTINI KOMPOSIT SEMOLINA DURUMPATI GANYONG DALAM PEMBENTUKAN SHORT CHAIN FATTY ACID DAN ASAM LAKTAT PADA FERMENTASI MENGGUNAKAN MIKROFLORA FESES MANUSIA - , STEFANI AMANDA HARMANI, Prof. Dr. Ir. Haryadi, M.App. Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Nowadays people has started considering the health beneficial value in selecting food. Governmentâs demand for utilization of local food and food diversification is also increasing. Considering those reason, the objective of this study was to create a way of food diversification using local ingredient which has physiological benefits for human health. Resistant starch can improve human colonic health through its fermentation by colonic microflora which produces Short Chain Fatty Acid (SCFA) and lactic acid. This research was conducted by combining canna starch with semolina durum into a composite flour for making spaghettini. Variations used were the variation in the type of canna tuber and the variation of canna starch proportion in flour composite. Semolina durum contained higher resistant starch (20%) than red canna starch (15.76%) and green canna starch (16.39%). Durum-canna based spaghettini had the ability to produce SCFA and lactic acid during in vitro fermentation using human colonic microflora although it was lower than the one produced by spaghettini made of 100% semolina durum. Spaghettini made of durum and red canna starch composite flour contained higher amount of resistant starch and SCFA-lactic acid than the one made of durum-green canna starch composite. Keywords: canna starch, spaghettini, resistant starch, SCFA, lactic acid